Modèles explicatifs de la créativité en traduction - Balacescu, Ioana; Stefanink, Bernd (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractUntil very recently it was possible to discard creativity from research in traductology on the basis that it could not be studied scientifically (Gerzymisch-Arbogast 1994: 16). With the destruction of the myth of objectivism (Lakoff with reference to non-occidental countries, Gadamer with reference to the Hermeneutic tradition) and the parallel evolution of traductology towards a taking into consideration of the personality of the translator, “intersubjective plausibility” (“Intersubjektive Nachvollziehbarkeit”, Stefanink 1997) has become a basic criterion in the assessment of translation quality. Recent cognitivistic research has fostered this evolution in so far as it has revealed the mechanisms of language management encouraging thus the translator to make use of his associative competence in looking for creative problem-solving within the limits of “intersubjective plausibility” which are fixed by the results of cognitivistic research.